Respiratory Manifestations of the Activated Phosphoinositide 3-Kinase Delta Syndrome - Condliffe, Alison M.; Chandra, Anita (Frontiers in Immunology, 2018)
The Activated Phosphoinositide 3-kinase δ Syndrome (APDS), also known as p110δ-activating mutation causing senescent T cells, lymphadenopathy and immunodeficiency (PASLI), is a combined immunodeficiency syndrome caused by gain-of-function mutations in the phosphoinositide 3-kinase (PI3K) genes PIK3CD (encoding p110δ: APDS1 or PASLI-CD) and PIK3R1 (encoding p85α: APDS2 or PASLI-R1). Whilst the disease is clinically heterogeneous, respiratory symptoms and complications are near universal and often severe. Infections of the ears, sinuses and upper and lower respiratory tracts are the earliest and most frequent manifestation of APDS, secondary to both respiratory viruses and to bacterial pathogens typical of defective B cell function. End organ damage in the form of small airways disease and bronchiectasis frequently complicates APDS, but despite documented T cell defects, opportunistic infections have rarely been observed. Antimicrobial (principally antibiotic) prophylaxis and/or immunoglobulin replacement have been widely used to reduce the frequency and severity of respiratory infection in APDS, but outcome data to confirm the efficacy of these interventions is limited. Despite these measures, APDS patients are often afflicted by benign lymphoproliferative disease, which may present in the respiratory system as tonsillar/adenoidal enlargement, mediastinal lymphadenopathy or mucosal nodular lymphoid hyperplasia, potentially causing airways obstruction and compounding the infection phenotype. Treatment with rapamycin and PI3Kδ inhibitors has been reported to be of benefit in benign lymphoproliferation, but hematopoietic stem cell transplantation (ideally undertaken before permanent airway damage is established) remains the only curative treatment for APDS.